Targeting the stimulator of interferon genes (STING) in breast cancer - Ying-Rui, Ma; Bu-Fan, Bai; Deng, Liu; Rong, Shi; Qian-Mei, Zhou (Frontiers in Pharmacology, 2023)
Breast cancer has a high occurrence rate globally and its treatment has demonstrated clinical efficacy with the use of systemic chemotherapy and immune checkpoint blockade. Insufficient cytotoxic T lymphocyte infiltration and the accumulation of immunosuppressive cells within tumours are the primary factors responsible for the inadequate clinical effectiveness of breast cancer treatment. The stimulator of interferon genes (STING) represents a pivotal protein in the innate immune response. Upon activation, STING triggers the activation and enhancement of innate and adaptive immune functions, resulting in therapeutic benefits for malignant tumours. The STING signalling pathway in breast cancer is influenced by various factors such as deoxyribonucleic acid damage response, tumour immune microenvironment, and mitochondrial function. The use of STING agonists is gaining momentum in breast cancer research. This review provides a comprehensive overview of the cyclic guanosine monophosphate-adenosine monophosphate synthase-STING pathway, its agonists, and the latest findings related to their application in breast cancer.